46 The relationship between high-sensitivity troponin taken on admission to critical care, regardless of whether there was a clinical indication for testing, and one year mortality: a novel biomarker for outcome?. (4th June 2021) - Hinton, Jonathan; Augustine, Maclyn; Gabara, Lavinia; Mariathas, Mark; Allan, Rick; Borca, Florina; Nicholas, Zoe; Gillett, Neil; Kwok, Chun Shing; Cook, Paul; Grocott, Michael; Mamas, Mamas; et al.
Abstract : Introduction: High-sensitivity troponin (hs-cTn) assays now form a key component of the diagnostic pathways for patients presenting to emergency medical services with chest pain. However, hs-cTn concentrations above the manufacturer-provided upper limit of normal (ULN) are now frequently reported in patients presenting with conditions not traditionally associated with type 1 myocardial infarction (T1MI). This is particularly true of severe illness states. We investigated the possible association between hs-cTn and one year mortality in critical care patients. Method: Consecutive patients admitted to two adult critical care units (general critical care unit (GCCU) and neuroscience critical care unit (NCCU)) over a six month period had hs-cTnI assay performed on admission, regardless of whether there was a clinical indication, and the results nested unless a clinical request had been made. Comorbidity data, illness severity and critical care outcome were recorded and have been previously reported. One year mortality data were obtained from NHS Digital. Results: After excluding patients diagnosed with T1MI by the clinical team, there were 1, 033 patients remaining. At one year a total of 253 (24.5%) patients had died. The Kaplan-Meier curves in figure 1 demonstrate a positive association between mortality and increasing hs-cTnI concentrations relative to the ULN. Specifically, using the log-rank test, the mortality at one year was significantly higher (p<0.001) in patients with hs-cTnI concentrations above the ULN. Furthermore, on multivariable Cox regression analysis, the log(10)hs-cTnI concentration was independently associated with the hazard of one year mortality (hazard ratio 1.587 (95% confidence interval 1.358 – 1.856). Conclusions: These data suggest that admission hs-cTnI is a biomarker for one year mortality in critical care patients. Further work is now required to assess whether any medical intervention can alter this risk. Conflict of Interest: All of these assays used in our studies were provided by Beckman Coulter but they had no other role in the studies